Implementasi Alat Ukur Suhu Dan PH Air Untuk Budidaya Lobster Dengan Algoritma Fuzzy Logic Berbasis IoT - Rahmi, Zulaida; Maulana, Rizky; Rialva, M. Nabil Risky (Journal of Computer Science and Information System(JCoInS), 2025)
Freshwater lobster cultivation has quite good business prospects, but the growth of the existing lobster cultivation business has not been in line with demand, this can be seen from the low production level and quality of aquaculture products. The quality of temperature and pH of the water can affect the activity in freshwater lobster cultivation, because one of the factors that affects the level of molting frequency and cannibalism. In order to overcome this problem, research was carried out to create a tool using fuzzy logic algorithms and combined with Internet of Things technology. Based on the results of the study by conducting tests 10 times, the average error value on the temperature sensor was 0.40% and the average error value on the pH sensor was 0.22%.